Metal oxide-polytetrafluoroethylene nano composite material, preparation method and application
By combining metal oxides with polytetrafluoroethylene to form metal oxides@polytetrafluoroethylene nanocomposites, the problem of poor acid oxidation resistance of noble metal catalysts in acid oxygen precipitation reaction is solved, and high-activity and long-term stable electrocatalytic water decomposition is achieved to produce hydrogen, reducing economic costs.
Patent Information
- Application Number
- CN202411956027.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-03-21
AI Technical Summary
Existing precious metal catalysts have poor acid oxidation resistance in acid oxygen precipitation reactions, and the scarcity of precious metals leads to high costs, making it difficult to achieve high activity and long-term stable electrocatalytic water decomposition to produce hydrogen.
By combining metal oxides with polytetrafluoroethylene, metal oxides@polytetrafluoroethylene nanocomposites are formed, the crystallization and growth of metal oxides are regulated, and the conductive network and coating structure are formed, and the activity and stability of the catalyst are improved.
High-activity and long-term stable electrocatalytic water decomposition and hydrogen production are achieved, reducing the amount of precious metals, significantly reducing the economic cost of hydrogen production, and maintaining high catalytic activity in harsh environments.
Smart Images

Figure CN119663339A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen production, and in particular to a metal oxide@polytetrafluoroethylene nanocomposite material and a preparation method thereof, and application thereof in the field of electrocatalytic hydrogen production. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] The continuous consumption of non-renewable energy has led to an increasingly urgent demand for clean, renewable and sustainable new energy. The earth has abundant water resources. Extracting hydrogen from water as a clean energy source can achieve zero carbon emissions. Therefore, the research on hydrogen production by electrolysis of water has become a hot topic. Proton exchange membrane water electrolyzer (PEMWE) has won wide attention due to its high energy efficiency, excellent hydrogen purity and broad industrial application prospects.
[0004] PEMWE is expected to usher in a new era of clean energy, but it still faces great challenges in designing highly active and durable electrocatalysts for acidic oxygen evolution reaction (OER). Currently, although precious metal catalysts show excellent intrinsic activity for OER, their acid oxidation resistance is poor. In addition, the scarcity of precious metals makes them expensive. Among all the methods to improve catalyst performance, constructing a specially structured supported catalyst as an effective method to improve acid oxidation resistance and reduce the precious metal content in the catalyst can effectively reduce the economic cost of hydrogen production. In the selection of carriers for supported catalysts, polytetrafluoroethylene, as a corrosion-resistant polymer binder widely used in acidic and alkaline electrode materials, has high application value, but its weak conductivity limits its application in the field of electrocatalyst synthesis. Summary of the invention
[0005] In order to realize the above technical concept, the present invention is designed to introduce polytetrafluoroethylene into metal oxides to improve their structure, aiming to reduce the size of metal oxide particles and promote the formation of defects, conductive networks and coating structures, thereby exposing more active sites and forming an acid-resistant and stable polytetrafluoroethylene coating layer, thereby improving the activity and stability of the catalyst, and ultimately obtaining an electrocatalytic water decomposition hydrogen production anode catalyst material with both high activity and long-term stability.
[0006] In order to achieve the above technical objectives, the present invention provides the following technical solutions: In a first aspect, a metal oxide@polytetrafluoroethylene nanocomposite material is provided, wherein the nanocomposite material comprises polytetrafluoroethylene particles and a metal oxide@polytetrafluoroethylene composite nanoparticle network supported on the polytetrafluoroethylene particles, wherein the specific surface area of the nanocomposite material is 33.9 to 61.9 cm -2 g -1 ; The metal oxide particle size is 6.5~43.6 nm, the metal content is 30.2~33.3 at.%, the oxygen content is 59.6~66.7 at.%, and the fluorine content is 0~10.2 at.% and is not 0.
[0007] The above at. % represents atomic percentage.
[0008] Polytetrafluoroethylene itself has good corrosion resistance and stability. As an engineering plastic, it can be processed into rods, tubes, strips, films, etc., and can perfectly cope with the highly corrosive working environment of the electrolytic water hydrogen production device. The present invention associates it with the use of it as a carrier and coating coat of metal oxides. It has been verified that in the temperature range of 300°C to 450°C, molten polytetrafluoroethylene can be used as a nucleation site and coating agent for metal oxides, regulating the crystallization and growth of metal oxides, and has the advantages of improving the crystal structure of metal oxides, promoting the formation of oxygen vacancies and coating interface structures, and is conducive to improving the reaction activity and stability of the catalyst.
[0009] In addition, it has been verified that the metal oxide@polytetrafluoroethylene composite nanoparticle network loaded on polytetrafluoroethylene particles can form a conductive network, which will help accelerate the charge transfer during the electrocatalytic reaction, allowing it to maintain a high catalytic activity even in harsh environments.
[0010] The above metal oxide is preferably a metal with high electrocatalytic activity, and currently commonly used electrocatalytic metals are iridium, ruthenium or platinum; preferably, the metal oxide is iridium oxide, ruthenium oxide or platinum oxide, selected from one or more thereof. Different types of metal salts result in different particle sizes and interface structures in the obtained nanocomposites, and there are certain differences in their physicochemical properties and stability, and there are certain differences in their electrochemical performance, but the performance is significantly better than the corresponding metal oxide nanomaterials. Therefore, those skilled in the art can choose according to their needs.
[0011] In a second aspect, a method for preparing the metal oxide@polytetrafluoroethylene nanocomposite material of the first aspect is provided, comprising the following steps: Add metal salt and water to polytetrafluoroethylene emulsion to obtain a precursor solution, and calcine at 300-450°C for 6-12 h to obtain the product.
[0012] The concentration of the polytetrafluoroethylene emulsion is 4-6 wt.%.
[0013] The metal salt is preferably iridium chloride, ruthenium chloride or platinum chloride, and more preferably ruthenium chloride.
[0014] The ratio of the above-mentioned polytetrafluoroethylene emulsion, metal salt and water is 4~7 μL: 20~50 mg: 0.8~1.2 mL.
[0015] In a third aspect, the present invention provides an application of the above-mentioned metal oxide@polytetrafluoroethylene nanocomposite material in the field of hydrogen production by water electrolysis.
[0016] The improved metal oxide@polytetrafluoroethylene nanocomposite material of the present invention has both high electrocatalytic oxygen evolution activity and acid resistance stability, and can be used as an anode material for a water electrolysis hydrogen production device. A feasible application method is to use it as an electrode material for PEMWE. In one embodiment verified by the present invention, the above-mentioned metal oxide@polytetrafluoroethylene nanocomposite material can be used as an anode catalyst for water electrolysis hydrogen production, showing a low overpotential (219 mV) and long-term stability (1.50 V, 800 h@10mA cm -2 ).
[0017] In a fourth aspect, the present invention provides an application of the above-mentioned metal oxide@polytetrafluoroethylene nanocomposite material in the field of hydrogen production by electrolysis of seawater.
[0018] The improved metal oxide @ polytetrafluoroethylene nanocomposite material of the present invention has both high electrocatalytic oxygen evolution activity and environmental tolerance, and can adapt to the highly corrosive working environment of in-situ electrolysis of seawater for hydrogen production. It can be used as an anode catalytic material for electrolysis of seawater for hydrogen production. A feasible application method is to use it as an electrode material for a seawater electrolyzer. In one embodiment verified by the present invention, the above-mentioned metal oxide @ polytetrafluoroethylene nanocomposite material can be used as an anode catalyst for electrolysis of seawater for hydrogen production, showing a low overpotential (237 mV) and long-term stability (1.52 V, 482 h@10 mA cm -2 ).
[0019] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a metal oxide@polytetrafluoroethylene nanocomposite material. In a water electrolysis hydrogen production performance test, the nanocomposite material has a high conductivity at 10 mA cm −2 At a current density of 1.5 V, the overpotential can be reduced to 219 mV, and the assembled device can stably electrolyze water to produce hydrogen for 800 h at a cell voltage of 1.50 V, showing excellent catalytic activity and stability. In addition, in the performance test of hydrogen production by electrolysis of seawater, the nanocomposite material has a high catalytic activity at 10 mA cm −2At a current density of 1.5 V, its overpotential can be reduced to 237 mV, and the selectivity of oxygen evolution is as high as 91.2%. The assembled device can stably electrolyze seawater to produce hydrogen for 482 h at a cell voltage of 1.52 V, showing excellent catalytic activity, selectivity and stability. Finally, the metal oxide @ polytetrafluoroethylene nanocomposite as an anode material effectively improves the dispersion of metal oxides and active sites, reduces the amount of precious metals, and significantly reduces the economic cost of electrocatalytic hydrogen production, which has broad commercial application prospects.
[0020] In addition, the present invention also provides a method for preparing the above-mentioned nanocomposite material: a precursor solution is obtained by mixing a metal salt solution with a polytetrafluoroethylene emulsion, and then calcining to obtain the nanocomposite material, forming a special structure of a polytetrafluoroethylene particle-loaded metal oxide@polytetrafluoroethylene composite nanoparticle network. The preparation method of the present invention uses direct calcination of wet mixed raw materials, which simplifies the preparation process of the supported metal oxide; and the preparation method has the advantages of scalability, low price and wide source of raw materials, simple preparation process, and easy industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0022] Figure 1 The SEM image of the metal oxide@polytetrafluoroethylene nanocomposite prepared according to the comparative example is shown.
[0023] Figure 2 The SEM image of the metal oxide@polytetrafluoroethylene nanocomposite prepared according to Example 1 is shown.
[0024] Figure 3 The morphology and composition characterization results of the metal oxide@polytetrafluoroethylene nanocomposite prepared according to Example 2 and Example 3 are shown: in, Figure 3 a is the SEM image of the metal oxide@polytetrafluoroethylene nanocomposite material in Example 2; Figure 3 b is the TEM image of the metal oxide@polytetrafluoroethylene nanocomposite material in Example 2; Figure 3 c is the HRTEM image of the metal oxide@polytetrafluoroethylene nanocomposite material in Example 2; Figure 3 d is the SEM image of the metal oxide@polytetrafluoroethylene nanocomposite material in Example 3; Figure 3 e is the TEM image of the metal oxide@polytetrafluoroethylene nanocomposite material in Example 3; Figure 3 f is the HRTEM image of the metal oxide@polytetrafluoroethylene nanocomposite material in Example 3; Figure 3 g is the Ru, O and F element mapping diagram of the metal oxide@polytetrafluoroethylene nanocomposite material in Example 2.
[0025] Figure 4 The SEM image of the metal oxide@polytetrafluoroethylene nanocomposite prepared according to Example 4 is shown.
[0026] Figure 5 The phase composition, oxygen defect and surface component characterization results of the metal oxide@polytetrafluoroethylene nanocomposite prepared according to Example 2 and Example 3 are shown; Among them, the sample of Example 2 is marked as RuO 2 -PTFE, the sample of Example 3 is marked as RuO 2 -F; Figure 5 a is the XRD diffraction pattern of the metal oxide@polytetrafluoroethylene nanocomposite material in Example 2 and Example 3; Figure 5 b and 5c are the EPR spectra of the metal oxide@PTFE nanocomposites in Example 2 (b) and Example 3 (c), respectively; Figure 5 d is the high-resolution XPS spectrum of Ru in the metal oxide@polytetrafluoroethylene nanocomposite material in Example 2 and Example 3; Figure 5 e is the high-resolution XPS spectrum of O in the metal oxide@polytetrafluoroethylene nanocomposite material in Example 2 and Example 3; Figure 5 f is the high-resolution XPS spectrum of F in the metal oxide@polytetrafluoroethylene nanocomposite material in Example 2 and Example 3.
[0027] Figure 6 The performance diagram of the metal oxide@polytetrafluoroethylene nanocomposite prepared according to Example 2 is shown as follows: in, Figure 6 a is the LSV curve; Figure 6 b is at 10 mA cm −2 The chronopotentiometry curve below. DETAILED DESCRIPTION
[0028] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0029] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0030] The present invention adopts a one-step calcination of wet mixed raw materials to prepare a metal oxide @ polytetrafluoroethylene nanocomposite electrode material, which has a network structure composed of ruthenium oxide nanoparticles, a high specific surface area, oxygen defects and a ruthenium oxide nanoparticle @ polytetrafluoroethylene thin layer coating structure, which integrates the high catalyst activity of precious metals and the acid resistance stability of PTFE, and its assembled device shows a high application potential in the electrolysis of water to produce hydrogen. Therefore, the present invention is very meaningful for developing efficient and stable electrocatalysts and improving the energy efficiency of electrocatalytic hydrogen production.
[0031] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.
[0032] The polytetrafluoroethylene emulsion used in the following examples is prepared as follows: a commercial 60 wt% polytetrafluoroethylene emulsion product is purchased and diluted with water.
[0033] Comparative Example (1) Add 1 mL of water and 20.7 mg of ruthenium chloride to a porcelain boat and stir to form a uniform precursor solution; (2) The precursor solution described in step (1) is placed in a muffle furnace and calcined at a temperature of 350°C for 6 h to obtain a metal oxide nanomaterial.
[0034] The microstructure of the prepared metal oxide nanomaterials is shown in Figure 1 shown.
[0035] Example 1 (1) Add 5 μL of 5 wt.% polytetrafluoroethylene emulsion to a porcelain boat; then add 1 mL of water and 20.7 mg of ruthenium chloride and stir to form a uniform precursor solution; (2) The precursor solution described in step (1) is placed in a muffle furnace and calcined at a temperature of 300°C for 12 h to obtain a metal oxide@polytetrafluoroethylene nanocomposite material.
[0036] The microstructure of the prepared metal oxide@PTFE nanocomposite is shown in Figure 2 shown.
[0037] Example 2 (1) Add 5 μL of 5 wt.% polytetrafluoroethylene emulsion to a porcelain boat; then add 1 mL of water and 20.7 mg of ruthenium chloride and stir to form a uniform precursor solution; (2) The precursor solution described in step (1) is placed in a muffle furnace and calcined at a temperature of 350°C for 6 h to obtain a metal oxide@polytetrafluoroethylene nanocomposite material.
[0038] The microstructure and composition distribution of the prepared metal oxide@PTFE nanocomposites are shown in Figure 3 As shown, denoted as RuO 2 -PTFE.
[0039] Example 3 (1) Add 5 μL of 5 wt.% polytetrafluoroethylene emulsion to a porcelain boat; then add 1 mL of water and 20.7 mg of ruthenium chloride and stir to form a uniform precursor solution; (2) The precursor solution described in step (1) is placed in a muffle furnace and calcined at 450°C for 6 h to obtain a metal oxide@polytetrafluoroethylene nanocomposite material.
[0040] The microstructure and composition distribution of the prepared metal oxide@PTFE nanocomposites are shown in Figure 3 As shown, denoted as RuO 2 -F.
[0041] Example 4 (1) Add 5 μL of 5 wt.% polytetrafluoroethylene emulsion to a porcelain boat; then add 1 mL of water and 41.5 mg of ruthenium chloride and stir to form a uniform precursor solution; (2) The precursor solution described in step (1) is placed in a muffle furnace and calcined at a temperature of 350°C for 6 h to obtain a metal oxide@polytetrafluoroethylene nanocomposite material.
[0042] The microstructure of the prepared metal oxide@PTFE nanocomposite is shown in Figure 4 shown.
[0043] Structural and compositional characterization The nanomaterials prepared in each case were subjected to BET specific surface area analysis, transmission electron microscopy metal oxide particle size analysis and X-ray photoelectron spectroscopy (XPS) surface composition analysis, and the structural and composition parameters are summarized in Table 1.
[0044] Table 1 Structure and composition parameters of nanomaterials prepared in each case As can be seen from Table 1, compared with the comparative example in which polytetrafluoroethylene is not added, the nanocomposites obtained by adding polytetrafluoroethylene in all the examples have higher specific surface areas and smaller ruthenium oxide nanoparticles. Reducing the calcination temperature (Examples 1 to 3) and the ratio of ruthenium chloride to polytetrafluoroethylene (Examples 2 and 4) can effectively reduce the size of ruthenium oxide nanoparticles. The nanocomposites obtained at a moderate calcination temperature (350°C) have the highest specific surface area (Examples 1 to 3). Reducing the ratio of ruthenium chloride to polytetrafluoroethylene can effectively increase the specific surface area of the nanocomposites (Examples 2 and 4).
[0045] The microstructure and composition distribution of the metal oxide@polytetrafluoroethylene nanocomposites prepared in Examples 2 and 3 are as follows: Figure 3 As shown. Figure 3 b and 3e can prove that the ruthenium oxide nanoparticles in the nanocomposite prepared at a moderate calcination temperature (350°C) are smaller and form a tightly connected network, while the ruthenium oxide nanoparticles in the nanocomposite prepared at a higher calcination temperature (450°C) are larger and form a loosely connected network. Figure 3 g proves that the surface of ruthenium oxide nanoparticles is coated with a thin layer of polytetrafluoroethylene.
[0046] The phase composition, oxygen defects and surface composition of the metal oxide@polytetrafluoroethylene nanocomposites prepared in Examples 2 and 3 are as follows: Figure 5 As shown. Figure 5 b and 5c can prove that there are oxygen defects in the nanocomposites prepared at a moderate calcination temperature (350 °C), while there are no oxygen defects in the nanocomposites prepared at a higher calcination temperature (450 °C).
[0047] The special structure and significant structural differences of nanomaterials have an important impact on the activity and stability of nanomaterials and their assembled devices.
[0048] Electrolyzed water oxygen evolution performance test The electrocatalytic oxygen evolution electrode was prepared by the following method: 5 mg of nanomaterials, 450 uL of ethanol and 50 uL of Nafion (Alfa Aesar, 5%) were mixed to prepare a uniformly dispersed catalyst ink (10 mg mL −1 ), and ultrasonicated continuously for 30 min. Then, the catalyst ink was dropped onto a glassy carbon (GC) electrode with a diameter of 5 mm, and 0.25 mg cm −2 The test electrode load was 0.5 MH 2 SO 4 Subsequent electrochemical tests were carried out in the electrolyte. The characteristic parameters of the electrocatalytic oxygen evolution activity of the nanomaterials prepared in each case are shown in Table 2.
[0049] Table 2 Characteristic parameters of electrocatalytic oxygen evolution activity of nanomaterials prepared in each case As shown in Table 2, compared with the comparative example without adding polytetrafluoroethylene, the nanocomposites prepared by adding polytetrafluoroethylene in all the examples showed higher activity: overpotential 219~265 mV, Tafel slope 61.2~69.6 mVdec -1 The nanocomposite prepared at a moderate calcination temperature (350 °C) exhibited the highest electrocatalytic oxygen evolution activity: overpotential 219 mV, Tafel slope 65.2 mV dec -1 (Examples 1 to 3) Reducing the ratio of ruthenium chloride to polytetrafluoroethylene can effectively enhance the electrocatalytic oxygen evolution activity of the nanocomposite material (Examples 2 and 4).
[0050] Electrolysis of seawater oxygen evolution performance test In order to further evaluate the potential of the nanocomposite material prepared in Example 2 for use as a hydrogen anode material for electrolysis of seawater, the oxygen evolution performance of the electrolysis of seawater was tested. The test method was similar to the test method for the electrolysis of water performance. It was only necessary to change the electrolyte from 0.5 MH 2 SO 4 The working electrode was replaced with seawater from the Yellow Sea, and the rotating disk electrode was used as the working electrode. The results showed that the overpotential of the nanocomposite prepared in Example 2 was 237 mV, and the Tafel slope was 68.3 mV dec. -1 ; at 10 mA cm -2 At a current density of 1.3 Å, the oxygen selectivity is as high as 91.2%.
[0051] Assembled device water electrolysis performance test (water electrolysis hydrogen production potential analysis) The electrocatalytic water splitting device was assembled by the following method: 5 mg of nanomaterials, 450 uL of ethanol, and 50 uL of Nafion (Alfa Aesar, 5%) were mixed to prepare a uniformly dispersed catalyst ink (10 mg mL −1 ) and continued ultrasonication for 30 min. Then, the catalyst ink was dropped to 1 cm 2 After natural drying, 1 mg cm −2 The anode electrode was used as the test electrode, and the commercial Pt / C catalyst was prepared by the same method as the cathode. 2 SO 4 Subsequent electrochemical tests were performed in the electrolyte. The performance characteristic parameters of the water splitting devices assembled with catalysts prepared in all embodiments and comparative examples are shown in Table 3. The performance data of the water splitting device assembled with nanocomposite materials prepared in Example 2 are shown in Table 3. Figure 6 shown.
[0052] Table 3 Performance characteristic parameters of water splitting devices assembled with nanomaterials prepared in each case Compared with the comparative example without adding polytetrafluoroethylene, the water decomposition voltage of the nanocomposite assembled devices prepared by adding polytetrafluoroethylene in all the examples is smaller (1.51-1.55V) and the stability is better (462-936 h@10 mA cm -2 ). Taking all factors into consideration, the nanocomposite assembled device prepared at a moderate calcination temperature (350 °C) exhibited the highest electrocatalytic water splitting activity and stability: the water splitting voltage was 1.50 V at 10 mA cm -2 The current density can be stable for 800 h (Examples 1~3, Figure 6 ). Reducing the ratio of ruthenium chloride to polytetrafluoroethylene can effectively improve the activity and stability of the nanocomposite assembled device for electrocatalytic water decomposition (Examples 2 and 4).
[0053] Seawater electrolysis performance test of assembled devices (analysis of hydrogen production potential by seawater electrolysis) In order to further evaluate the potential of the nanocomposite assembled device prepared in Example 2 for in-situ electrolysis of seawater to produce hydrogen, the electrolysis performance of the assembled device was tested. The test method was similar to the electrolysis performance test method of water. It was only necessary to change the electrolyte from 0.5 MH 2 SO 4 The results showed that the assembled device can -2 At a current density of 1.52 V, seawater can be electrolyzed to produce hydrogen for 482 h.
[0054] Combined with the structural relationship analysis, the nanocomposite material prepared in Example 2 has a tightly connected network composed of smaller ruthenium oxide nanoparticles, a higher specific surface area, oxygen defects and a thin layer of polytetrafluoroethylene coating covering the ruthenium oxide nanoparticles, which significantly improves its electrocatalytic activity and stability.
[0055] In summary, the calcination temperature and the ratio of ruthenium chloride to polytetrafluoroethylene have an important influence on the structure of metal oxide@polytetrafluoroethylene nanocomposites, the electrocatalytic oxygen evolution performance and the electrocatalytic water decomposition performance of nanocomposite assembled devices, thereby significantly affecting the application potential of nanocomposites in the field of hydrogen production.
[0056] In addition, although exemplary embodiments have been described herein, the scope includes any and all embodiments based on the present invention with equivalent elements, modifications, omissions, combinations (e.g., various embodiments intersecting schemes), adaptations or changes. The elements in the claims are to be interpreted broadly based on the language used in the claims, and are not limited to the examples described in this specification or during the practice of the invention, which examples are to be interpreted as non-exclusive. Therefore, this specification and examples are intended to be considered as examples only, and the true scope and spirit are indicated by the following claims and the full scope of their equivalents.
[0057] The above description is intended to be illustrative rather than restrictive. For example, the above examples (or one or more of them) may be used in combination with each other. For example, a person of ordinary skill in the art may use other embodiments when reading the above description. In addition, in the above-mentioned specific embodiments, various features may be grouped together to simplify the present invention. This should not be interpreted as an intention that a feature of an application that does not require protection is necessary for any claim. On the contrary, the subject matter of the present invention may be less than all the features of an embodiment of a particular application. Thus, the following claims are incorporated herein as examples or embodiments in the specific embodiments, wherein each claim is independently a separate embodiment, and it is considered that these embodiments can be combined with each other in various combinations or arrangements. The scope of the present invention should be determined with reference to the appended claims and the full scope of equivalent forms granted by these claims.
[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A metal oxide@polytetrafluoroethylene nanocomposite material, characterized in that: The nanocomposite material comprises polytetrafluoroethylene particles and a metal oxide@polytetrafluoroethylene composite nanoparticle network supported on the polytetrafluoroethylene particles. The specific surface area of the nanocomposite material is 33.9-61.9 cm -2 g -1 ; The metal oxide particle size is 6.5~43.6 nm, the metal content is 30.2~33.3 at.%, the oxygen content is 59.6~66.7 at.%, and the fluorine content is 0~10.2 at.% and is not 0.
2. The metal oxide@polytetrafluoroethylene nanocomposite material as claimed in claim 1, characterized in that: The metal oxide is a metal element with high electrocatalytic activity, selected from iridium, ruthenium or platinum; preferably, the metal oxide is iridium oxide, ruthenium oxide or platinum oxide, selected from one or more thereof.
3. The method for preparing the metal oxide@polytetrafluoroethylene nanocomposite material according to claim 1 or 2, characterized in that: The steps include: Add metal salt and water to polytetrafluoroethylene emulsion to obtain a precursor solution, and calcine at 300-450 °C for 6-12 h to obtain the product.
4. The preparation method according to claim 3, characterized in that: The concentration of the polytetrafluoroethylene emulsion is 4-6wt.%.
5. The preparation method according to claim 3, characterized in that: The metal salt is preferably iridium chloride, ruthenium chloride or platinum chloride, and more preferably ruthenium chloride.
6. The preparation method according to claim 3, characterized in that: The ratio of the polytetrafluoroethylene emulsion, the metal salt and water is 4~7 μL: 20~50 mg: 0.8~1.2 mL.
7. Application of the metal oxide@polytetrafluoroethylene nanocomposite material prepared by the preparation method according to claim 1 or 2 or any one of claims 3 to 5 in the field of hydrogen production by electrolysis of water.
8. The use according to claim 7, characterized in that The metal oxide@polytetrafluoroethylene nanocomposite material is used as an anode material for a water electrolysis hydrogen production device.
9. The metal oxide@polytetrafluoroethylene nanocomposite material prepared by the preparation method according to claim 1 or 2 or any one of claims 3 to 5 is used as an anode material for a hydrogen production device by electrolyzing seawater.
Citation Information
Patent Citations
Ultrathin honeycomb layered oxide nanosheet, preparation method and application of ultrathin honeycomb layered oxide nanosheet in electrocatalytic acidic oxygen evolution reaction
CN116375113A
Electrocatalyst for seawater electrolysis hydrogen production as well as preparation method and application of electrocatalyst
CN118996494A